Effects of dietary Silphium perfoliatum L. on the growth performance, immunity, intestinal health, and resistance against Nocardia seriolae of largemouth bass (Micropterus salmoides) - Tang, Hao; Luo, Sheng; Chen, Jifeng; Zhou, Qianjin; Yang, Guanjun; Lu, Jianfei; Chen, Jiong (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the effect of dietary Silphium perfoliatum L. on growth performance, immunity, intestinal health, and resistance against Nocardia seriolae of largemouth bass. Four dietary concentrations of S. perfoliatum L. were prepared: 0% (SPL0), 1% (SPL1), 2.5% (SPL2.5), and 5% (SPL5). After 60 d feeding, a challenge test was conducted by injecting N. seriolae intraperitoneally. The results showed that supplementing the diets with S. perfoliatum L. could promote the weight gain rate, specific growth rate, and feed intake. Meantime, S. perfoliatum L. could also enhance the activity of immune-related enzymes and improve the expression of immune-related genes in the liver. Compared to the control group, S. perfoliatum L. improved intestinal morphology and reduced the abundance of harmful bacteria in intestinal microbiota. Importantly, supplementing the diets with S. perfoliatum L. protected largemouth bass from N. seriolae infection, resulting in a relative percent survival (RPS) of 24% (SPL1), 31.99% (SPL2.5), and 43.99% (SPL5). In conclusion, the present study showed that S. perfoliatum L. could boost growth performance, enhance immunity, promote intestinal health, and improve the ability of largemouth bass against N. seriolae infection.